Metal-dependent properties of metallothionein. Replacement in vitro of zinc in zinc-thionein with copper. - Suzuki, K T (1981)
Metal-dependent changes in the properties of metallothionein were investigated in vitro by replacing Zn2+ in zinc-thionein with Cu+ and Cu2+. Metallothionein was separated into isoproteins on a gel-permeation column by elution with alkaline buffer solution, the separation being due to the dissociation of hydroxy groups in the gel material. The two metals in metallothioneins were detected simultaneously by introducing the eluate of the column, which was attached to a high-pressure liquid chromatograph, to two flame atomic-absorption spectrophotometers. Zn2+ in zinc-thionein was replaced with 1.5 and 1 mol. equiv. of Cu+ and Cu2+ respectively. The replacement with Cu2+ accompanied intramolecular oxidation of thiol groups in metallothioneins and the oxidized metallothioneins showed different chromatographic properties from the original ones, probably due to changes in the isoelectric points. The oxidized forms of metallothionein were reducible by mercaptoethanol. Reduction of Cu2+ to Cu+ followed by the replacement of Zn2+ in zinc-thionein with Cu+ occurred in the presence of glutathione.